The 1st Fukuoka Asian Art Triennale 1999. - Fukuoka Asian Art Museum, Fukuoka; Asian Art Triennale Fukuoka 1999; Choi, Eunju; Choudhury, Subir; Chung, Junmo; Daravuth, Ly; Gunaratna, D.M.; Hashmi, Salima; Hideki, Nakamura; Hildawa, Isidro, G.; Jin, Yuqing; Kanha, Sikounnavong; et al. (Fukuoka : Fukuoka Asian Art Museum, 1999)
Ahmed, Kamal ; Alesworth, David ; Altaf, Navjot ; An Sitha ; Aquilizan, Alfredo J.D. ; Blupers / Rhie Joongjae ; Chen Shunchu ; Chhachhi, Sheba ; Choi Jian ; Chunmok, Lee ; Dadi, Elizabeth ; Dadi, Iftikhar ; Daravuth, Ly ; Esquillo, Alfredo D. Jr. ; Faizal Mohd Zulkifli ; Feng Mengbo ; Gupta, Subodh ; Heng, Amanda ; ium ; Kallat, Jitish ; Karma ; Karmakar, Ashoke ; Kazi, Durriya ; Khanthavilay, Douangdy ; Le Quang Ha ; Leki Dorji ; Lin, Michael ; M.P.P. Yei Myint ; Matzain, Mahaddi B. Hj. ; Muan, Ingrid ; Murti, Krisna ; Nair, Surendran ; Nguyen Minh Thanh ; Noor Azizan Rahman Paiman ; Nyein Chan Su ; Pg. Zainin B. Pg. Mansor ; Phy Chan Than ; Po Po ; Prom Sam An ; Ritsuko, Taho ; Ser-Od Sarantsatsralt ; Setiadikara, Chusin ; Shigeaki, Iwai ; So Chenda ; Svay Ken ; Tang Dawu ; Thammavong, Phauvanh ; Thenuwara, Chandraguptha ; Tiravanija, Rirkrit ; Tissa de Alwis ; Toemsombat, Montri ; Tsuyoshi, Ozawa ; Uma Shankar Shah ; Vannara, Soeung ; Wagley, Shobha ; Wang, Jun-Jieh ; Wong Hoy Cheong ; Wu Tien-chang ; Xu Bing ; Zagdin Usehbayar ; Zhang Peili ; Zhuang Hui
ind. tent., gr. tent. p. 298-309
Engels
Japans
1st Fukuoka Asian Art Triennale 1999, FAAM (Fukuoka Asian Art Museum) Fukuoka, 06.03. - 06.06.1999
boek